2018
DOI: 10.1186/s12879-018-3608-5
|View full text |Cite|
|
Sign up to set email alerts
|

Nasopharyngeal carriage of Streptococcus pneumoniae in children under 5 years of age before introduction of pneumococcal vaccine (PCV10) in urban and rural districts in Pakistan

Abstract: BackgroundBenefits of pneumococcal conjugate vaccine programs have been linked to the vaccine’s ability to disrupt nasopharyngeal carriage and transmission. The 10-valent pneumococcal vaccine (PCV10) was included in the Expanded Program on Immunization (EPI) in Sindh, Pakistan in February 2013. This study was carried out immediately before PCV10 introduction to establish baseline pneumococcal carriage and prevalent serotypes in young children and to determine if carriage differed in urban and rural communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
4
16
2
Order By: Relevance
“…This serotype distribution is rather different from that described in similar studies. We found a much higher proportion of children with the serotype 7B/7C/40, while the proportion of children we identified with the serotypes 19F, 6A or 6B was considerably lower than in similar studies (proportion of serotypes in children sick with respiratory symptoms) [7,17,41,42,44] or among healthy children in communitybased carriage studies [43,[45][46][47][48]. In the neighbouring context of India, 6A/B and 19F were also found to be the most prevalent serotypes in children admitted with clinical pneumonia, together with serotypes 14 and 23F.…”
Section: Discussioncontrasting
confidence: 85%
“…This serotype distribution is rather different from that described in similar studies. We found a much higher proportion of children with the serotype 7B/7C/40, while the proportion of children we identified with the serotypes 19F, 6A or 6B was considerably lower than in similar studies (proportion of serotypes in children sick with respiratory symptoms) [7,17,41,42,44] or among healthy children in communitybased carriage studies [43,[45][46][47][48]. In the neighbouring context of India, 6A/B and 19F were also found to be the most prevalent serotypes in children admitted with clinical pneumonia, together with serotypes 14 and 23F.…”
Section: Discussioncontrasting
confidence: 85%
“…We previously reported a pneumococcal carriage prevalence of 64% in children aged 12-24 months old in the Bandung region, suggesting that carriage rates stabilize after 12 months in this population (Dunne et al, 2018). Carriage prevalence tended to be higher in infants living in semi-rural areas than in urban residents, as observed in some, but not all, other studies (Hanieh et al, 2014;Nisar et al, 2018). Previously, we did not observe differences in pneumococcal carriage between urban and semi-rural Indonesian children aged 12-24 months, suggesting that differences diminish with age (Fadlyana et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…We looked at indirect effect in two ways- first in the form of decline in the unvaccinated group over the course of four years. Secondly, we calculated a more formal measure of indirect effect by comparing VT carriage in the unvaccinated group (0 dose) with the pre-introduction VT carriage [14] . This is a slightly different approach from other studies reported in literature where the comparison is made usually with the adult population, older children or the group too young to be vaccinated or a concurrent population where the vaccine has not been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we aim to describe impact of PCV10 on pneumococcal carriage in vaccinated (direct protection) and unvaccinated children (indirect or herd protection) aged less than two years in a rural population in Matiari, Sindh, Pakistan. We use point estimate of 26.7% as the baseline Vaccine Type (VT) carriage from a pre-introduction carriage survey in the same population [14] . We also describe the socio-demographic and clinical characteristics associated with VT carriage.…”
Section: Introductionmentioning
confidence: 99%